Case report: Cardiac myxoid fibrosarcoma: a report of two cases - Dong, Weikai; Du, Zhaoqi; Liu, Dianxiao; Yang, Lijuan; Li, Wei (Frontiers in Oncology, 2025)
IntroductionThe research into cardiac tumors can be traced back to the 18th century, when Bonet first introduced the relevant concept. It was not until 1936 that the first successful resection of a cardiac tumor was performed. From a pathological origin perspective, cardiac tumors can be categorized into two main types: primary tumors, which originate from the heart itself, and secondary tumors, which result from metastases of malignant tumors in other tissues or organs. Primary cardiac tumors are exceedingly rare, among primary cardiac tumors, roughly 75% are benign, while the remainder are malignant. In contrast, approximately 75% of primary malignant cardiac tumors are sarcomas. Cardiac myxoid fibrosarcoma stands out as a particularly rare diagnosis in this domain.Case reportCase one: A 25-year-old man presented with chest pain and tightness. After initial treatment, his symptoms recurred and worsened. Imaging revealed a large mass in the left atrium obstructing the mitral valve. He underwent surgical resection of the tumor, thrombectomy, and tricuspid valvuloplasty. Pathology diagnosed myxoid fibrosarcoma. The patient was readmitted 7 months later with hemoptysis due to tumor recurrence and was lost to follow-up after symptomatic treatment. Case two: A 67-year-old woman was admitted with cough, chest tightness, and shortness of breath. Physical examination and imaging showed a mass in the left atrium causing mitral valve obstruction. She underwent surgical resection of the tumor. Pathology confirmed myxoid fibrosarcoma. After 6 months of follow-up, there was no tumor recurrence or metastasis.DiscussionMyxoid fibrosarcoma located in the left atrium can lead to mitral valve obstruction, causing symptoms of mitral stenosis such as dyspnea, cough, hemoptysis, and reduced exercise tolerance. Surgery remains the primary treatment for primary left atrial malignant tumors. Once the diagnosis is confirmed, active surgical intervention should be performed to relieve blood flow obstruction, remove pericardial effusion, and alleviate cardiac compression, which can extend patients’ lives in the short term and improve their quality of life. Despite advancements in diagnostic techniques and surgical methods, the prognosis for patients with cardiac tumors still depends on the histology and location of the tumor.